Study on method of distinguishing influence factors for vector modulation errors measurement - Hong FANG; Xin ZHOU; Ke LIU; Xin BIAN (Tongxin xuebao)
In order to distinguish between the intrinsic modulation errors of vector signal generator and the measurement errors of vector signal analyzer,a method based on experimental measurement and analytical calculation was proposed,then numberical simulation and actual measurement were presented for verification.This method can not only improve accuracy and reliability of calibration for vector signal generator and vector signal analyzer,but also provide some theoretical basis for the establishment of traceability in the measurement of digital modulation quality parameters.